2020
DOI: 10.1177/1465312519899671
|View full text |Cite
|
Sign up to set email alerts
|

Managing orthodontic appliances in everyday life: A qualitative study of young people’s experiences with removable functional appliances, fixed appliances and retainers

Abstract: Objective: To compare young people’s experiences of wearing a range of orthodontic appliances. Design: A cross-sectional, qualitative study with purposive sampling. Setting: UK dental teaching hospital. Participants: Twenty-six orthodontic patients aged 11–17 years. Methods: Patients participated in in-depth semi-structured interviews. All interviews were transcribed verbatim and analysed thematically. Results: Young people reported physical, practical and emotional impacts from their appliances. Despite these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Functional Aligners Retainers (for example Essix appliance) Functional appliances are used by growing patients to guide the correct growth of the dento-alveolar complex and the jaws [5].…”
Section: Removable Appliancesmentioning
confidence: 99%
“…Functional Aligners Retainers (for example Essix appliance) Functional appliances are used by growing patients to guide the correct growth of the dento-alveolar complex and the jaws [5].…”
Section: Removable Appliancesmentioning
confidence: 99%
“…This removable and easily washable oral device can also encourage better oral hygiene and better oral health status [38]. One of the main advantages of the proposed approach is the low psychosocial and psychological impact on the patient [39].…”
Section: Discussionmentioning
confidence: 99%
“…Kettle et al 34 identified from young people a multi-dimensional social process of managing everyday life with an orthodontic appliance. This study only included subjects wearing buccal fixed appliances; therefore, the impact of other removable appliances, retainers, or lingual brackets was not measured with the OHIP-S14 Ortho, and the results are not generalizable to all kinds of orthodontic treatment.…”
Section: Ohip-s14 Ortho Validationmentioning
confidence: 99%
“…Another factor to take into account is the response scale used in this study. Although it is easily quantifiable and understood, it might not measure the true attitudes of respondents, which could underestimates the effects of impacts of high concern to individuals, as the impact of the malocclusion is largely in the emotional and social well-being subscales 34 .On the other hand, our study analysis approach was by classical test theory (CTT) instead of the item response theory (IRT), based on the notion that CTT does not invoke a complex theoretical model to relate an examinee's ability to succeed on a particular item and that is easier to apply in many testing situations. However, readers must be aware of the weakness of CTT in terms of its circular dependency on item/person statistics.…”
Section: Ohip-s14 Ortho Validationmentioning
confidence: 99%